Seasonal and Morphological Controls on Nitrate Retention in Arctic Deltas. Issue 7 (1st April 2023) - Knights, Deon; Piliouras, Anastasia; Schwenk, Jon; Hariharan, Jayaram; Russoniello, Christopher
Abstract: Estimates of nitrate loading to the Arctic Ocean are limited by the lack of field observations within deltas partly due to logistical constraints. To overcome this limitation, we use a remote sensing framework to estimate retention of nitrate in Arctic deltas. We achieve this by coupling hydrological and biogeochemical process models at the network scale for five major Arctic deltas. Binary masks of delta channels were used to simulate flow direction and magnitude through networks. Models were parameterized using historical and seasonal observations. Simulated nitrate retention ranged from 2.9% to 15% of the incoming load. Retention rates were largest during winter but smallest during spring conditions when increased discharges export large nitrate masses to the coast. Under future climate scenarios, retention rates fall by ∼1%–10%. Arctic deltas have an important effect on the magnitude of nitrate entering Arctic seas and the inclusion of processing in deltas can improve flux estimates. Plain Language Summary: The Arctic Ocean is the smallest and shallowest of the world's oceans but receives the largest riverine input per basin volume. Thus, the flux of nitrate from land to sea through rivers in the circumpolar Arctic can have large impacts on coastal life and global biogeochemical cycles. To assess the impact of terrestrially derived nitrate on Arctic Ocean chemistry under current and future scenarios, accurate accounting of nitrate loading is needed. Deltas act as filters that reduce nitrate loads, but current estimates of flux exclude the effects of Arctic deltas on nitrate export. We use a novel approach based on satellite imagery to estimate the potential impact of deltas on nitrate retention on five Arctic deltas, representing a range of morphologies and sizes. Our analysis shows seasonal and morphological differences in nitrate processing rates in each delta with retention rates ranging from 2.9% to 15% of incoming load and most retention occurring during winter months. Under future climate scenarios, the efficiency of nitrate retention decreases by up to 10%. Our models suggest that Arctic deltas alter the magnitude of nitrate entering the ocean and future predictions of loading or current earth system models could be improved by incorporating their effect. Key Points: Remotely sensed data provide a useful tool for revealing patterns of nitrate retention in Arctic deltas Channel networks of Arctic deltas are most efficient at retaining nitrate during spring and winter Hotspots of nitrate removal cluster according to network structure and discharge on Arctic deltas